Reconsideration in ICSID arbitration: a procedural mechanism promoting the correctness of awards - Aragonés Molina, Laura (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
In the last years several arbitral tribunals constituted according to the ICSID Convention and Rules have ruled on a potential power to reconsider preliminary decisions issued in bifurcated or trifurcated proceedings (jurisdiction, merits and quantum). The most recent arbitral practice has favored the recognition of this power changing the legal position previously maintained. The different interpretations made by these arbitral tribunals on the res judicata principle and their inherent powers allow us to reflect on two main questions; on the one side, the implications of the consolidation of such a power for the current system of remedies foreseen in the ICSID normative framework; and, on the other side, the problems of coherence inside the ICSID system as well as in relation to General International Law.